Behind the church revolution - Plenc, Daniel Oscar (2012)
Critical analysis of recent publications Russell Burrill in relation to the mission andleadership of the Adventist Church A review of these writings in the light of theBible, writings of Ellen White and contemporaneous missiologists authors.